The Effect Of The Marketing Mix Service On Loyalty Of Customers With The Satisfaction Of Service As Intervening Variables In Pt Mandala Multifinance Padang City - Sigit Sanjaya; Susi Yuliastanty (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This study aimed to analyze: (1) The effect of services marketing mix to satisfaction on services, (2) The effect of services marketing mix to customer loyalty (3) The effect satisfaction on services to customer loyalty (4) The effect services marketing mix to customer loyalty through satisfaction on service as intervening variable. This type of research is causative, the respondents are customers of Mandala Finance Padang City. The population in this study amounted to 2868 people. Determination of the number of samples by using Slovin Formula, samples were taken with Simple Random Sampling method. This study used sample of 352 people Mandala Finance Customer. Type of this research is the primary data. Primary data in this study were obtained from questionnaires distributed to respondents. Data were analyzed using descriptive and inductive analysis through Structural Equation Model analysis and hypothesis testing using t test (α = 0.05). The research show that: (1) Product, price and physical evidence have significant effect to satisfaction on services (2) Product and price have significant effect to customer loyalty (3) satisfaction on services have significant effect to customer loyalty (4) Product and price have significant effect to customer loyalty through satisfaction on services as an intervening variable.